Construction of yeast microbial consortia for petroleum hydrocarbons degradation - Wang, Minzhen; Zhou, Mengyu; Li, Hengchang; Cao, Zhibei; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2024)
Microbial degradation of petroleum hydrocarbons plays a vital role in mitigating petroleum contamination and heavy oil extraction. In this study, a Saccharomyces cerevisiae capable of degrading hexadecane has been successfully engineered, achieving a maximum degradation rate of up to 20.42%. However, the degradation ability of this strain decreased under various pressure conditions such as high temperature, high osmotic pressure, and acidity conditions. Therefore, a S. cerevisiae with high tolerance to these conditions has been constructed. And then, we constructed an “anti-stress hydrocarbon-degrading” consortium comprising engineered yeast strain SAH03, which degrades hexadecane, and glutathione synthetic yeast YGSH10, which provides stress resistance. This consortium was able to restore the degradation ability of SAH03 under various pressure conditions, particularly exhibiting a significant increase in degradation rate from 5.04% to 17.04% under high osmotic pressure. This study offers a novel approach for improving microbial degradation of petroleum hydrocarbons.